Morphological, anatomical, and molecular notes on two neglected high-altitude taxa of the genus Limax (Stylommatophora: Limacidae) from North Macedonia and their unusual adaptation to extreme alpine conditions - Dedov, Ivaylo K.; Schneppat, Ulrich E.; Glogger, Fabia Knechtle; Cornu, Regula; Hristovski, Slavčo; Borissov, Simeon (Zootaxa, 2025)
The article examines two neglected taxa of the genus Limax—Limax macedonicus macedonicus P. Hesse, 1928 and Limax macedonicus leucopus P. Hesse, 1928. Presently, both are accepted as junior synonyms of Limax graecus Simroth, 1889. This study describes the ecological differences and confirms the most important morphological, as well as some small but stable differences in the structure of the reproductive systems between both taxa and L. graecus. The conclusion that we are dealing with two separate valid taxa is supported by molecular data.